A biointerface effect on the self-assembly of ribonucleic acids: a possible mechanism of RNA polymerisation in the self-replication cycle. Issue 12 (12th March 2020) - Arai, Noriyoshi; Kobayashi, Yusei; Yasuoka, Kenji
Abstract : The self-assembly was found to be more favoured in a vesicle-cell membrane, rather than in the bulk system. The result will contribute to a better understanding of the origin of life on the primitive Earth. Abstract : Despite decades of intensive research, many questions remain on the formation and growth of the first cells on Earth. Here, we used computer simulation to compare the self-assembly process of ribonucleic acids in two environments: enclosed in a vesicle-cell membrane and in the bulk. The self-assembly was found to be more favoured in the former environment, and the origin of such a biointerface effect was identified. These results will contribute to a better understanding of the origin of life on the primitive Earth.